The influence of digital twins on the methods of film and television creation. (October 2022) - Li, Liang
Abstract: All walks of life in the world have entered the "big data era", and China's film and television industry is also developing rapidly. Digital twins can also have a huge impact on how film and television are created. This paper aims to study the theoretical knowledge of digital twins and film and television creation methods, and propose an image and video super-resolution reconstruction algorithm based on video computing and reconstruction. Both algorithms make perfect sense in digital twins. This paper proposes how to study the impact of digital twins on the way of film and television creation. It can be seen from the data in Table 1 of the experiment in this paper that the director's attention to the way of film and television creation has increased from 54% in 2013 to 70% in 2019. It can be seen that the decoding quality of the two reconstruction algorithms is higher than that of the traditional reconstruction algorithm. It can be seen that it is very meaningful to explore the impact of digital twins on the way of film and television creation.Digital twin is a multi-disciplinary, multi-physical, multi-scale, multi-probability simulation process that makes full use of physical models, sensor updates, and operating history to complete the mapping in virtual space, thereby reflecting the full life cycle of the corresponding physical equipment. process. A digital twin is a concept beyond reality that can be viewed as a digital mapping system of one or more important, interdependent equipment systems.